The Role and Influence of Tuan Guru on The Development of Islamic Education in Lombok: An Ethnographic Study of Islamic Education of The Sasak Tribe in The 19th Century - Murdianto, Murdianto; Nasihin, Sirajun (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2022)
This study explores the role and influence of Tuan Guru in the development of Islamic education in Lombok, especially among the Sasak community in the 19th century. With an ethnographic approach, this study explores how Tuan Guru, as a religious figure and educator, shaped the map of Islamic education in the Sasak community. This study uses an ethnographic approach with data collection methods, namely participant observation, semi-structured in-depth interviews. While the data analysis technique used is constructivist grounded theory developed by Charmaz. This process involves (1) coding, namely data is coded openly, axially, and selectively to identify main themes and patterns. (2) Constant comparison, namely themes and categories that emerge will continue to be compared and integrated to develop a data-based theory. (3) Memo-writing, researchers will make analytical memos throughout the research process to facilitate theory development. The results of the study show that Tuan Guru plays an important role in introducing and expanding Islamic education, both formal and non-formal, in the Sasak environment, which was previously dominated by animist and Hindu-Buddhist practices. Through the establishment of Islamic boarding schools and madrasahs, Tuan Guru not only spread Islamic teachings, but also introduced literacy and modern education to the community. This finding confirms that the implications of Tuan Guru's presence in Sasak society go beyond the religious dimension and bring about significant socio-cultural transformation in Sasak society.